An Implementation of Head Up Position to Trauma Brain Injury Patients on the Level of Consciousness - Nurfajri, Qurrata A’yunnin Fitra; Yunanto, Rismawan Adi (Jurnal Kegawatdaruratan Medis Indonesia, 2023)
Traumatic brain injury is a leading cause of death among motorized vehicle users and is caused by a failure to maintain road safety. Traumatic brain injury can result in physical, psychological, and even fatal changes. Patients with head injuries may experience impaired consciousness due to bleeding in the head, which causes an increase in intracranial pressure. Nursing interventions such as head positioning at 30° may be given to patients with traumatic brain injuries. To examine the implementation of giving a 30° head-up position to the level of consciousness in patients with traumatic brain injury. The results obtained from giving the patient a 30° head-up position are that the patient has an increased level of consciousness. The patient's level of consciousness at the initial assessment was GCS E2 VX M5, and nursing intervention was carried out by giving the head-up position 30° for three days, namely E4 VX M5. Giving a head-up position of 30° affects the level of consciousness in patients with traumatic brain injury.